Statutory adjudication: A global trend for resolution of payment problems in construction industry - Raji, Barakat Adebisi; Ali Mohamed, Ashgar Ali; Mohammed, Nurah Sabahiah (International Islamic University Malaysia, 2017)
This paper examines the reality of payment problems bedeviling the stakeholders in the construction industry and the enormity of the threat that it poses in the delivery of projects in general and the economic development in particular in Nigeria. It x-rays the causes and effects of and possible solutions to this problem as well as the attempts that have been made to tackle the menace through the instrumentality of law at the international level and at the domestic level. The paper identifies, among others, the report of the project audit commission set up in year 2013 to investigate on the federal government abandoned projects which revealed that over 12,000 projects awarded by the federal government of Nigeria had been abandoned across the country while those of the states were even worse especially with the present economic recession while the deleterious effects of this phenomenon such as loss of lives, unemployment among others are also catalogued. Interview was conducted to collect in order to identify the causes of this payment problem. Hence, Fifteen (15) construction experts were interviewed consisting of legal practitioners, stakeholders and judges who have been into construction practice for more than ten (10) years were selected using purposive technique to get rich data. The findings revealed the inadequacy of the legal framework for construction dispute resolution in Nigeria. This has led to the abandonment of many of the projects across the country as well as claiming the lives and properties of some stakeholders. Hence, the paper suggests a number of ways through which these challenges can be tackled with the adoption of statutory adjudication act which has assisted many of the construction industry in other commonwealth countries to regain its lost glory. In conclusion, the paper makes certain recommendations for Nigeria such as the need to revisit the legal framework for construction dispute resolution and enact a law and modification of the existing laws guiding the resolution of construction disputes in Nigeria to accommodate statutory adjudication as a lasting solution to payment problems in construction industry.